2020
DOI: 10.2174/1570180817666200129143803
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of 4-ethoxychalcones on Oxidoreductase/Pirin Inhibitors and Cytotoxic Evaluation on Breast/Skin Cancer Cell Lines

Abstract: Background: The role of α, β unsaturated propenone derivatives has attracted the chemists for its biological importance. An attempt is made to know the interaction with breast and skin cancer cell lines along with molecular docking studies. Objective: To synthesize and characterize 4-ethoxychalcones for testing towards breast and skin cancer targets. Method: A series of chalcone analogues starting from 4-ethoxyacetophenone and substituted aromatic aldehydes were synthesized, well characterized and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…When compared to other reported chalcones tested on different melanoma cell lines, we found that compound 12 is two times more active than those of the ethoxy-chalcones class, studied by Harshitha et al [36], where the best derivative showed an IC 50 value of 53.47 µM for A-375 metastatic melanoma cell line. On the other hand, compound 12 was found to be less active than the synthesized chalcone-sulfonamide hybrids reported by Castaño et al [37], most of them possessing activities against LOX IMVI melanoma cell line, with IC 50 values between 0.34 and 0.54 µM.…”
Section: Antimelanoma Activitiesmentioning
confidence: 48%
“…When compared to other reported chalcones tested on different melanoma cell lines, we found that compound 12 is two times more active than those of the ethoxy-chalcones class, studied by Harshitha et al [36], where the best derivative showed an IC 50 value of 53.47 µM for A-375 metastatic melanoma cell line. On the other hand, compound 12 was found to be less active than the synthesized chalcone-sulfonamide hybrids reported by Castaño et al [37], most of them possessing activities against LOX IMVI melanoma cell line, with IC 50 values between 0.34 and 0.54 µM.…”
Section: Antimelanoma Activitiesmentioning
confidence: 48%
“…Another reported class refers to ethoxychalcones; these were studied by Harshitha and collaborators (2020) [ 51 ] and were obtained by classic aldol condensation. The best compound was derivative ( 28 ) ( Figure 7 ), which showed IC50 value = 53.47 μM for breast cancer cell line MDA-MB-231 and metastatic melanoma cells (A-375).…”
Section: Chalcones With Anticancer Activitymentioning
confidence: 99%